The Importance of Patient's Experience and Its Impact on Health Care System for People Receiving Traditional Chinese Medicine. - Chiou, Shang-Jyh; Lee, Pei-Chen; Lee, Li-Hui; Lin, Kuan-Chia (Journal of Alternative & Complementary Medicine, 2020)
Objectives: Health system responsiveness is a complicated issue that guides researchers in determining an efficient methodology to enhance the understanding of health care systems' perspectives. This study examined the relationship between patients' experience profiles and their satisfaction with medical outcomes. Design: The authors used 11 items from the Taiwanese Annual National Health Insurance survey and used latent class analysis (LCA) to develop experience profiles for 2012 Traditional Chinese Medicine (TCM) patients. A logistic regression model was developed to explore differences in patients' satisfaction with their treatment outcome across four groups identified using the LCA, with adjustment for demographic factors. Subjects: Patients' experiences with medical services in TCM in 2015. Outcome measures: Patients' satisfaction with their treatment outcome. Results: Participants (N = 2012) were divided into four groups. Regardless of gender and age, Group 2 (nall) held the lowest satisfaction with treatment outcome relative to those reported by the other three groups (odds ratios with p-value: Group 1 [pall]: 7.40, Group 3 [nComm]: 1.37, Group 4 [Skip]: 2.20, p < 0.001). Respondents with a more favorable patient experience reported higher satisfaction with treatment outcome. Conclusions: An increased favorable treatment experience in TCM (such as positive accessibility and better interpersonal relationships with providers) is associated with higher satisfaction with treatment outcome. The World Health Organization emphasizes that traditional medicine integrated with Western medicine can play an important role in achieving the goal of "Health for All." Health authorities should develop strategies aimed at enhancing patients' experiences in TCM to contribute to a positive care process.